Storyline 360 y su aporte en el aprendizaje en los estudiantes de bachillerato técnico en informática de la Unidad Educativa Prócer José de Antepara periodo académico Octubre 2024 – Marzo 2025 - Arreaga Leon, Karen Liliana (2025)
Digital tools are transforming our current society and their application in education is increasingly important, this article focuses on one of them in particular, such as analyzing the contribution of Storyline 360 in learning in technical high school students in computer science at the Prócer José de Antepara educational unit for the academic period October 2024 - March 2025. Where we will explore how students interact with Storyline and its impact on motivational skills and self-regulation that are essential in the digital world. The research will be descriptive and explanatory, focused on understanding how Storyline 360 is used in the autonomous learning of technical high school students in computer science, the results obtained use a mixed approach that combines qualitative and quantitative data to achieve a complete discernment of the event, the numerical data will identify the results of the use of Storyline 360, while the qualitative data is adjusted to a detailed and contextualized understanding. On the other hand, desk research is based on the collection and analysis of existing information in books, articles and reports, which is essential to support the data and obtain reliable results on the impact of Storyline on student learning.